Anti-Methanogenic Potential of Seaweeds and Impact on Feed Fermentation and Rumen Microbiome In Vitro - Pradeep Kumar Malik; Atul Purshottam Kolte; Shraddha Trivedi; Govindan Tamilmani; Archit Mohapatra; Shalini Vaswani; Johnson Belevendran; Artabandhu Sahoo; Achamveetil Gopalakrishnan; Raghavendra Bhatta (Microorganisms)
A series of in vitro studies were conducted to explore the anti-methanogenic potential of five seaweeds collected from the Indian sea and to optimize the level(s) of incorporation of the most promising seaweed(s) into a straw and concentrate diet to achieve a significant reduction in methane (CH4) production without disturbing rumen fermentation characteristics. A chemical composition analysis revealed a notable ash content varying between 55 and 70% in seaweeds. The crude protein content was highly variable and ranged between 3.25 and 15.3% of dry matter. Seaweeds contained appreciable concentrations of tannins and saponins. Among the seaweeds, Spyridia filamentosa exhibited significantly higher CH4 production, whereas the percentage of CH4 in total gas was significantly lower in the cases of Kappaphycus alvarezii and Sargassum wightii. The ranking of seaweeds in terms of CH4 production (mL/g OM) is as follows: Sargassum wightii < Kappaphycus alvarezii < Acanthophora specifera < Padina gymnospora < Spyridia filamentosa. A remarkable decrease of 31–42% in CH4 production was recorded with the incremental inclusion of Kappaphycus alvarezii at levels of 3–5% of the dry matter in the diet. The addition of Sargassum wightii led to a significant decrease of 36–48% in CH4 emissions when incorporated at levels of 4–5% of dry matter, respectively. The findings of this study revealed a significant decrease in the numbers of total protozoa and Entodinomorphs, coupled with increasing abundances of sulfate-reducing microbes and minor methanogens. Metagenome data revealed that irrespective of the seaweed and treatment, the predominant microbial phyla included Bacteroidota, Bacillota, Pseudomonadota, Actinomycetota, Fibrobacterota, and Euryarchaeota. The prevalence of Methanobrevibacter was similar across treatments, constituting the majority (~79%) of the archaeal community. The results also demonstrated that the supplementation of Kappaphycus alvarezii and Sargassum wightii did not alter the feed fermentation pattern, and therefore, the reduction in CH4 production in the present study could not be attributed to it. Animal studies are warranted to validate the extent of reduction in CH4 production and the key processes involved by supplementation with Kappaphycus alvarezii and Sargassum wightii at the recommended levels.